Analisis Kesalahan Mahasiswa Teknik Pertambangan Menurut Kriteria Watson dalam Menyelesaikan Soal Kalkulus Integral - Sastrowijoyo Sastrowijoyo (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to identify the types of errors made by Mining Engineering students when solving integral calculus problems, based on Watson’s error taxonomy. This research employed a descriptive qualitative approach, with three research subjects selected through purposive sampling. The selection was based on students' varying ability levels, high, medium, and low, and their communication skills in expressing ideas. The findings reveal that students made various types of errors in line with Watson’s criteria. High-ability students made errors such as irrelevant data (id), omitted data (od), and omitted conclusion (oc). Medium-ability students committed errors such as incorrect procedure (ip), unwarranted manipulation (um), and omitted conclusion (oc). Meanwhile, low-ability students made more complex errors, including incorrect procedure (ip), omitted conclusion (oc), response level conflict (rlc), and skills hierarchy problem (shp). Factors contributing to these errors include lack of conceptual understanding, inaccuracy in reading the questions, forgetting integral formulas, and weak mastery of problem-solving steps. These findings are expected to contribute to improving the teaching methods of integral calculus in higher education, particularly in Mining Engineering programs.